KAMPANYE MICROGREENS MELALUI INSTAGRAM DALAM MEMPERINGATI HARI TANI INDONESIA - Aldi Adi Pratama; Kaniaareta Sadya Zafira; Kiki Yulianto (LPPM UNIMA, 2022)
This Community Service activity aims to create an understanding of microgreens in commemorating Indonesian Farmer's Day on September 24. Microgreens are mini plants that have many health benefits. Microgreens comes from the words micro (small) and greens (forage) which are harvested from 7 days to 14 days. The project was carried out through a persuasive communication system Instagram campaign, with the help of volunteers. Instagram was chosen because based on previous research by CupoNation, Indonesia is ranked 4th with the most Instagram users in the world as many as 56 million. Has evolved into a platform that allows users to create a visual identity for businesses. The campaign includes understanding, content, types, health benefits, differences with sprouts, advantages, cultivation, opportunities, suitable microgreens to plant, processed microgreens, bioprospects, and duration lighting microgreens. The author's analysis can conclude that persuasive communication methods are said to be very efficient in microgreens campaigns. This can be seen from the follower analysis of volunteers' Instagram, 45 users said they understood very well and 42 others said they understood, even though there were negative data.campaign system tends to be interesting, because it provides solutions and understanding based on current problems, such as the economy during and after a pandemic